(untitled) (Altre Modernità, 2019)
Julio Carrasco, Fuimos a bombardear Croacia (Santiago de Chile, Penguin Random House Grupo Editorial Chile, 2014, 130 pp. ISBN 978-956-347-759-7) por Marianna Montanaro